عہد اسلام کے چند منتخب شعرا کی شاعری کا جائزہA Review of the Poetry of a few Selective Poets of the Islamic Era (Al-Qamar, 2023)
The topic of this research based on the critical analysis of a few selected poets of Islamic Era. This is a historical and narrative way of research. It aims to introduce and analyze the literary work of the ancient Muslim poets who contributed in the literary history of the world. The history of Arabic language (literature) covers a long period. The Arabs were famous for their poems, sermons, etc. Based on this, they used to call other nations dumb and deaf. In the Arab region, poetry singing, chanting, and rhyming were permanent arts. The Arab people used to say that such fine weight and rhyme did not exist in any other region of the world. There are such instances in imagery, metaphor, and simile that the human mind is stunned. The first formal beginning of poetry in Arabia is found with Amr al-Qais, after which other poets also made their mark. After the poets, comes the period of veterans, after this comes the era of the Islamic poets (the Umayyad era). Some Islamic poets will be mentioned in this magazine. His brief life circumstances will be described, and the characteristics of his poetry will be clarified. An example will be given with each feature. There will be an introduction to the poets in an easy-to-understand manner. This article also consists abstract, key words, Data analysis, conclusion and references.
Keywords: Poetry; Poets; Islamic Age; Arab; literature